The Role of Rumah Tahfiz Al-Qur’an in Preventing Juvenile Delinquency and Instilling Islamic Values - Susi Lestari Siregar; Saiful Akhyar Lubis; Mohammad Al Farabi (Ta'dib)
This study aims to analyze the Rumah Tahfiz Al-Qur'an (RTQ) program to prevent deviant behavior in adolescents in Kisaran Timur District, Asahan Regency. This study uses a descriptive qualitative method using data collection techniques through in-depth interviews, observations, and document studies. The results of the study indicate that there are several deviant behaviors in adolescents in Kisaran Timur District, Asahan Regency, including premarital sex, drug use, theft, gambling, brawls, and violations of school rules. These deviant behaviors are generally caused by a lack of parental supervision and understanding of religious values. In an effort to prevent the spread of deviant behavior among adolescents, the RTQ program plays an important role in shaping the character of the younger generation. The RTQ program that can improve character formation, namely strengthening the values ​​of responsibility, honesty, and discipline, providing spiritual and emotional guidance, establishing regulations for the use of gadgets, and encouraging students to be optimistic in gaining knowledge. From this, RTQ can reduce the level of social deviation in adolescents if parents are willing to give their children trust to follow all programs in RTQ to the maximum.